The level of parental involvement in early childhood development in Nkulumane B cluster in Mzilikazi district - Balanda, Nobuhle (Midlands State University, 2018)
Parental involvement in children’s education remains low, despite evidence that parents have a huge influence on children’s achievement. Major researchers in the field have identified many factors that may create barriers to parental involvement and also suggested the solutions. Through interviews and questionnaires this study examined aspects of parental involvement in the education of Early Childhood Education (ECE) learners in Nkulumane Cluster in Bulawayo. The study will provide schools with objective data that will allow stakeholders to identify specific and effective strategies to increase parental involvement. The researcher explored the levels of parental involvement in the education of ECE learners. Using generally a qualitative approach, the researcher investigated the impact of parental involvement in Early Childhood Education, the views of school teachers on parental involvement in Early Childhood Education and how much the parents were involved in Early Childhood Education.